Update breast cancer 2020 part 2 - advanced breast cancer: new treatments and implementation of therapies with companion diagnostics - Lüftner, Diana; Schneeweiss, Andreas; Hartkopf, Andreas; Müller, Volkmar; Wöckel, Achim; Janni, Wolfgang; Ettl, Johannes; Belleville, Erik; Schütz, Florian; Thill, Marc; Huober, Jens; Fasching, Peter Andreas; et al. (Geburtshilfe und Frauenheilkunde, 2020)
For patients with locally advanced or metastatic breast cancer, new and effective therapies such as CDK4/6 inhibitors, PARP inhibitors and a PD-L1 inhibitor have been introduced in recent years. This review presents an update on the available studies with their data. In addition, two innovative anti-HER2 therapies are presented (trastuzumab-deruxtecan and tucatinib) for which the results from new studies have been reported. Molecular tests offer the possibility of defining patient populations or also monitoring courses of therapy. This can help identify patients with specific characteristics in order to provide them with individually targeted therapy within the framework of studies. In a large study, the benefit of such a biomarker study was able to be described for the first time.